Efficacy and safety of phenytoin versus clobazam as monotherapy for newly diagnosed epileptic patients - Dey, Saborni; Kem, Anil Kumar; Yatish,; Agarwal, Somya (Asian Journal of Medical Sciences, 2022)
Background: Epilepsy is a chronic disorder characterized not only by recurrent seizures but also by a great variety of medical and psychosocial implications. Its burden to the patients and their families has been recognized and even the impact upon the community is vast. Aims and Objectives: The aim of the study was to compare the efficacy and safety of phenytoin and clobazam in monotherapy for the management of new onset, untreated epileptic patients. Materials and Methods: A 6 months, observational, comparative study was conducted on 60 adult patients with epilepsy. The eligible patients were given either phenytoin sodium (Group A; n=30) in a loading dose of 15 mg/kg orally, followed by 5 mg/kg/day maintenance dose for 6 months while Group-B (n=30) received clobazam in a dose of 1 mg/kg oral loading dose followed by 0.5 mg/kg/day. Seizure frequency was evaluated and compared with baseline at 1, 2, 3, 4.5, 6 months along with adverse drug reaction assessment. Results: In Group A mean pre-treatment baseline seizure frequency was 6.3±2.19 and for Group B 5.80±2.22. After 6 months, seizure frequency for Group A 2.30±1.99 and in Group B 1.30±1.91. In Group B, there was a significantly higher reduction in seizure frequency (P=0.001) than that of Group A. Both the drug groups significantly reduced the seizure frequency but Group B was found to be superior. Adverse drug reaction was more in Group A in comparison with Group B. The common side effects were drowsiness, weight gain, headache, tiredness, nausea and ataxia. Conclusion: Clobazam monotherapy had demonstrated better efficacy than phenytoin for the treatment of epilepsy and also well tolerated.